Italy : Financial Sector Assessment Program-Technical Note-Banking Regulation and Supervision and Bank Governance. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This note presents a targeted review of selected aspects concerning the regulation and supervision of banks in Italy and their governance framework. The review was carried out as part of the 2019 Italy Financial Sector Assessment Program (FSAP) and was based on the regulatory framework in place and the supervisory practices employed as of March 2019. Since the regulation and supervision of significant banking institutions (SIs), including Italian SIs, was extensively covered as part of the 2018 Euro Area FSAP, this note focuses on the prudential regulation and supervision of less significant institutions (LSIs). In addition, the note reviewed regulatory and supervisory areas not covered by the wider EU regulatory framework, such as the supervision of anti-money laundering and countering the financing of terrorism (AML/CFT) and related party transactions, which apply to both SIs and LSIs in Italy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet